Digital Literacy Curriculum in Elementary School - Rizal Kailani; Rudi Susilana; Rusman Rusman (Teknodika, 2021)
Advances in technology and information have an impact on the ease and abundance of various information resources that are obtained digitally and are not limited so that all levels of education need to adapt to technological advances including elementary schools in managing curriculum and learning. The purpose of this research is to find out how digital literacy is in elementary schools. The research method uses a systemic literature review by analyzing 15 relevant articles on digital literacy in elementary schools and 10 article about curriculum digital literacy. Research findings show that the digital literacy curriculum is carried out by integrating digital literacy in all areas of the school. In the implementation of learning, elementary school students still consider the teacher as the only source of information. Therefore, it is necessary to have a collaborative role between teachers, principals and parents in integrating digital literacy in learning and overcoming something unwanted. Digital literacy in elementary schools places more emphasis on media literacy in learning which has an impact on interactive and collaborative learning, one of which is video, stop-motion and social media. Indirectly digital literacy can improve student learning outcomes.